Seasonality influences skin bacterial community structure and anti-Bd function in two anuran species - Zhang, Han; Ma, Hongying; Deng, Jie; Zhao, Hu; Fang, Cheng; Zhang, Jianlu; Wang, Qijun; Zhang, Hongxing; Jiang, Wei; Kong, Fei (Frontiers in Microbiology, 2024)
Microorganisms on amphibian skin reduce disease susceptibility and play an important role in pathogen defense. We hypothesized that anuran skin bacterial communities would change in response to seasonal variation and host species. To test this hypothesis, we used 16S rRNA amplicon sequencing to identify cutaneous bacterial communities of two frogs from the Qinling Mountains of China, Pelophylax nigromaculatus and Nanorana quadranus. We matched the amplicon sequence variants (ASVs) of microbes exhibiting protective effects against the pathogen Batrachochytrium dendrobatidis (Bd), using a database containing over 1900 16S rRNA gene sequences from amphibian skin bacteria. The results showed that seasonal variation had a stronger effect than host species on the structure (alpha-diversity, beta-diversity, species composition and abundance, and biomarkers) and anti-Bd function of cutaneous bacterial communities. These communities were highly dynamic but varied similarly between hosts. Their structural similarities were more consistent at the phylum level, but markedly less so at finer taxonomic levels. The highest relative abundance of anti-Bd reads was observed in P. nigromaculatus during summer, but anti-Bd reads were present in both frog species during different seasons. Therefore, the protective function of cutaneous microbial communities appears to be continuous despite between-species differences in anti-Bd ASV abundance. This observation does not directly explain why Bd infections have not been recorded in the region, butprovides important insight on anuran pathogen defense mechanisms. Our findings also suggest that specific seasons can be periods of high infection risk, with major implications for research on amphibian ecology and conservation.